Leptospira seroprevalence detection and rabies virus absence in an urban raccoon (procyon lotor) population in a highly populated area, Costa Rica - Hernández Mora, Gabriela (2019)
Leptospirosis and rabies are zoonotic diseases of public health importance and endemic diseases in tropical countries such as Costa Rica. Peridomestic wild animals such as raccoons (Procyon lotor) have been implicated as competent hosts of Leptospira spirochetes and rabies virus. This study focused on understanding the role of urban raccoons in the dynamics of leptospirosis and rabies in a tropical environment. A total of 97 specimens of the common raccoon were captured within the Greater Metropolitan Area of Costa Rica; 32.6% (31/95) of raccoons presented evidence of antibodies (> 1: 100) against Leptospira sp. Attempts to cultivate Leptospira failed, but 19 serovars were identified, which are also responsible for causing disease in humans in Costa Rica. Detected titers ranged from 1: 100 to 1: 6400. Lymphoid hyperplasia in kidneys and spirochetes were dem- onstrated in 3 of 20 necropsied cases (15%). Twenty brain samples were analyzed by hematoxylin and eosin stain for evidence of encephalitis and Negri body detection and simultaneously frozen brain material was employed to perform a rapid immunoassay test for rabies antigen. All tested samples were negative. This study is the first report of Leptospira seroprevalence in raccoons that cohabit urban areas in Costa Rica. We also highlight the importance of the raccoon as one of their natural competent host and sentinel animals within highly populated urban environments in tropical cities.